MANAGEMENT OF AUTISM SPECTRUM DISORDER WITH ABHAYAGHRITA AND PANCHA BHAUTIKA TAILANASYA- A CASE REPORT - *Praveen Kumar Sharma,; Agrawal, Manisha; Arun Kumar, Mahapatra; S, Rajagopala (International Journal of Ayurveda and Pharma Research, 2019)
Autism Spectrum Disorder (ASD) is a lifelong neurodevelopmental condition with its onset before the age of three years. It is characterized by abnormalities in communication, impaired social function, repetitive behaviours and restricted interests. There is no effective treatment currently available for ASD and there is a growing need of an alternative treatment modality. A three year six month old male patient, diagnosed with ASD was brought to the OPD for Ayurvedic treatment of ASD. There is no mention of ASD in Ayurveda classics and hence, considered an Anukta Vyadhi. ASD involves vitiation of all the three Doshas mainly Vata Dosha in the lead. The management was primarily based on the associated Doshas and Ayurvedic formulations i.e. Abhaya Ghrita orally for three months and Marsha Nasya with Panchabhautika Taila for forty five days were used. Changes in the clinical features were assessed using Aberrant Behaviour Checklist (ABC) and changes in the severity of disease after treatment was done using Clinical Global Impression scale (CGI). The patient showed significant improvement in the core features of ASD after the treatment duration.